Androgen receptor inhibition sensitizes glioblastoma stem cells to temozolomide by the miR-1/miR-26a-1/miR-487b signature mediated WT1 and FOXA1 silencing - Ana Belén Díaz Méndez; Marta Di Giuliani; Andrea Sacconi; Elisa Tremante; Valentina Lulli; Marta Di Martile; Giulia Vari; Francesca De Bacco; Carla Boccaccio; Giulia Regazzo; Maria Giulia Rizzo (Cell Death Discovery)
Abstract Glioblastomas (GBMs) are aggressive brain tumors and challenging cancers for diagnosis and treatment. Therapeutic options include surgery followed by chemotherapy with the DNA alkylator temozolomide (TMZ) and radiotherapy. However, the patient's prognosis remains poor due to tumor heterogeneity, cell infiltration and intrinsic or acquired resistance to therapy. Understanding the resistance mechanisms together with identifying new biomarkers are crucial for developing novel therapeutic strategies. MiRNAs play an important role in the biology of gliomas, they modulate tumorigenesis and therapy response. We recently identified the diagnostic/prognostic miR-1-3p, miR-26a-1-3p and miR-487b-3p signature that displays an oncosuppressive role on several glioma biological functions. In this study, we investigated the effects of the therapeutic potential of this three-miRNA signature as a regulator of response to TMZ. We found that ectopic expression of the miRNA signature in patient-derived GBM neurospheres treated with TMZ impaired cell proliferation and viability by necroptosis induction. Moreover, we identified WT1 and FOXA1, two transcription factors specifically involved in TMZ resistance, as novel direct targets of the miRNA signature. Of note, the repression of WT1 and FOXA1, elicited by the signature, caused a downregulation of the Androgen Receptor (AR) expression, an impairment of tumor-spheroid formation and reversed cancer cell stemness. These results were recapitulated using the AR inhibitor enzalutamide, confirming the involvement of the AR pathway. Our data indicate that the miR-1-3p/miR-26a-1-3p/miR-487b-3p signature, which has an impact on treatment response and cell stemness, may pave the way for miRNA-based complementary therapies in GBM patients.